2014
DOI: 10.1097/mpa.0000000000000104
|View full text |Cite
|
Sign up to set email alerts
|

Interlude of cGMP and cGMP/Protein Kinase G Type 1 in Pancreatic Adenocarcinoma Cells

Abstract: The cGMP and PKG signaling may be a target for developing new therapeutic approaches for PDAC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 26 publications
0
17
0
Order By: Relevance
“…Panc02 cells were treated 48 h with different concentrations of SkQ1. After that viability and proliferation assays were performed as described elsewhere …”
Section: Methodsmentioning
confidence: 99%
“…Panc02 cells were treated 48 h with different concentrations of SkQ1. After that viability and proliferation assays were performed as described elsewhere …”
Section: Methodsmentioning
confidence: 99%
“…Cell viability after gem treatment was measured with a EZ4U Kit (Biomedica, Austria) in the whole medium as described elsewhere [23]. Briefly, for the EZ4U assay 20,000 cells per well were seeded in 96-well plates.…”
Section: Cell Viability Assaysmentioning
confidence: 99%
“…It has been demonstrated that the basal activity of PKG is essential for preventing spontaneous apoptosis of cancer cells (Fraser et al 2006). Recently, our group has found out that the PKG inhibitor DT3 can reduce the viability and proliferation as well as migration of human PDAC cells in vitro (Karakhanova et al 2014a), pointing to the therapeutic potential of PKG inhibition for PDAC. DT3 is a specific membrane-permeant peptide-based inhibitor of PKG.…”
Section: Introductionmentioning
confidence: 98%